(3GdHUGFQ hGdPNGFQs - (3Ydj Hf eMeO Hf GdYHGS GdJhMjOj, CHh MjGf,J (B400 (3g` s
(3ChdgG (B:s
(3Gddge Efc GdMb GdeHjf gPG GdLRA GdKGfi HUGFQ GdbOeGA s
(3BNQgG (B:s
(3Ydi CKQg Ef UQaJ YJHc ai LeY eG YQV ef GdfaS , hOd Ydi GdYLR s
(3GdfSNI HgG MhGTs
(3ef GdfSNI GdSGHbIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B205 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B684s
Keywords: (3GdCOHs